2011
DOI: 10.1007/s11095-011-0563-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Monoclonal Antibodies: Relation Between the Second Virial Coefficient (B 2) at Low Concentrations and Aggregation Propensity and Viscosity at High Concentrations

Abstract: B (2) can be used, within certain limitations, as an effective indicator of viscosity and aggregation propensity of highly concentrated MAb solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 42 publications
(60 reference statements)
5
135
0
Order By: Relevance
“…More importantly, we have provided examples where aggregation does not correlate with conformational stability and native-state protein-protein interactions. As such, there will be limited utility of using k D values as a predictor for aggregate growth rates in the absence of strong electrostatic interactions [7,78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, we have provided examples where aggregation does not correlate with conformational stability and native-state protein-protein interactions. As such, there will be limited utility of using k D values as a predictor for aggregate growth rates in the absence of strong electrostatic interactions [7,78].…”
Section: Discussionmentioning
confidence: 99%
“…A decreasing k D value is often correlated with increased aggregation propensity when reducing electrostatic repulsion by increasing ionic strength or using a salt or buffer ion that neutralizes protein charge [35,46,57,74,78,82,19,46,63,77,81]. Consistent with these studies, for the wild-type, SB and DSV mutants, the relative rates of aggregate growth (as reflected by the corresponding T SLS ⁄ values) and protein-protein interactions (as reflected by the k D values) decrease non-specifically upon addition of NaCl due to screening of electrostatic interactions.…”
Section: Correlations Between K D and Aggregation Propensitymentioning
confidence: 99%
“…Saito et al 38 suggested the following general guideline: Antibodies with B 22 greater than 2£10 ¡5 mL mol per gm 2 have solution viscosities lower than 20 cP at 150 mg per mL, provided B 22 and viscosity measurements are performed in the same formulation. 38 In a separate study, Connolly et al 39 40 In the data from Binabaji et al, mAbs that met the B 22 criterion of Saito et al had low solution viscosities at 150 mg per mL. However, Binabaji et al also reported that B 22 is insufficient to predict solution viscosities when mAb concentrations rise above 200 mg per mL.…”
Section: Theoretical Foundations and Experimentally Measurable Quantimentioning
confidence: 99%
“…Herein, B 2 was determined from three concentrations less than 10 mg/mL in solutions of varying pH for three different MAbs. All MAbs, MAb-A, MAb-B, and MAb-C, are humanized IgG 1 which have the same constant region and different variable regions (Saito et al 2012). B 2 determined by AUC-SE at different pH values is shown in Fig.…”
Section: Predictions Of Aggregation Propensity and Viscosity At High mentioning
confidence: 99%